Trends in Renal Function Among Heart Transplant Recipients of Donor-Derived Hepatitis C Virus. Issue 5 (May 2020) - Zalawadiya, Sandip K.; Lindenfeld, JoAnn; Shah, Ashish; Wigger, Mark; Danter, Matthew; Brinkley, D. Marshall; Menachem, Jonathan; Punnoose, Lynn; Balsara, Keki; Brown Sacks, Suzanne; Ooi, Henry; Perri, Roman; et al.
Abstract : Donor-derived hepatitis C (dd-HCV) infection may increase the risk of renal impairment (RI) among heart transplantation (HT) recipients. Sofosbuvir, an integral component of HCV direct-acting antivirals (DAAs) has also been linked to RI. To date, no study has examined the trends in renal function for HT recipients of dd-HCV infection and assessed safety and efficacy of Sofosbuvir-based DAAs. Between September 2016 and June 2018, 46 HCV-naive patients and one patient with a history of HCV treated pretransplant, underwent HT from HCV-positive donors (follow-up available through October 10, 2018). Patients were treated with Ledipasvir-Sofosbuvir (genotype 1) or Sofosbuvir-Velpatasvir (genotype 3) for 12 or 24 weeks; no dose adjustments were made for renal function. Data on renal function were available for 23 patients who achieved a sustained virologic response at 12 weeks after the treatment (SVR12; cohort A) and 18 patients who completed 1 year of follow-up (cohort B). Treatment of dd-HCV infection was initiated at a median of 6 weeks post-HT. In both cohorts, a nonsignificant reduction in median estimated glomerular filtration rate (eGFR; ml/min/1.73 m 2 ) was noted (cohort A: pretransplant eGFR: 62 [interquartile range IQR: 1–84] to SVR12 eGFR: 49 [IQR: 37–82]; p = 0.43; cohort B: pretransplant eGFR: 65 [IQR: 54–84] to 1 year post-HT eGFR: 56 [IQR: 39–75]; p = 0.29). Pretreatment renal function had no significant impact on changes in renal function during treatment. All patients tolerated DAAs well with 100% completion rate to the assigned therapy and duration and 100% success at achieving SVR12. In this first and largest reported case series to date of HT recipients with dd-HCV infection, we observed that neither the dd-HCV infection nor its treatment with Sofosbuvir-based DAAs increased the risk of RI. Sofosbuvir-based DAAs appear safe, tolerable, and effective for HCV treatment even in presence of severe RI. Abstract : Supplemental Digital Content is available in the text.